Purification and characterization of a novel extracellular Streptomyces lividans 66 enzyme inactivating fusidic acid. - von der Haar, B (1995)
The wild-type strain Streptomyces lividans 66 is resistant against the steroid-like antibiotic fusidic acid. Comparative studies of the wild-type strain and a fusidic acid-sensitive mutant allowed the identification of an extracellular enzyme which inactivates fusidic acid. With the help of a combination of ultrafiltration and chromatographies with Phenyl-Sepharose and an anion exchanger, the enzyme was highly purified. Its apparent molecular mass is 48 kDa, its optimal activity ranges between 45 and 55 degrees C, and its optimal pH is 6.0 to 9.0. It is stimulated by neither monovalent nor divalent ions. The enzyme acts as a specific esterase which removes the acetyl group at C-16 from fusidic acid. The resulting intermediate is unstable, and spontaneous lactonization between C-21 and C-16 occurs rapidly.